(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper the concept of nano topology is studied in a different way . The notation of nano -open is established. Also the concept -covering dimension is defined. The aim of this paper is to introduce and define a new type of covering dimension by using nano -open sets namely, a nano -covering dimension in a nano topological space and find some relations to other concepts. Some properties and characterization of this covering dimension are obtained.